Innovation in the Operation of Art Institutions Guided by Public Participation and Improvement of Cultural Governance Efficiency - Song, Yanxing (International Journal of Social Sciences and Public Administration, 2025)
In the context of modernizing the cultural governance system, art institutions, as the core carriers of public cultural services, are transforming from "elite led" to "public participation". Public participation oriented operational innovation is the key to breaking through the homogenization dilemma and expanding audience coverage for art institutions, and it is also an important support for improving cultural governance efficiency. This article is based on the theory of cultural governance and public participation practice, combined with the transformation practice of domestic art institutions. It systematically analyzes the inherent relationship between the two from five aspects: transformation logic, innovation dimension, empowerment mechanism, practical difficulties, and optimization path. It explores how to strengthen the public service attributes of art institutions through innovation such as spatial openness, content co creation, and channel expansion, and achieve precision, diversification, and sustainability of cultural governance. Research has shown that building an operational system of "government guidance, institutional leadership, public participation, and social collaboration" can deeply integrate art institutions into social governance, becoming an important force in consolidating cultural consensus, cultivating cultural ecology, and enhancing social civilization.